Сравнительная характеристика функции щитовидной железы у грызунов, приспособленных к засушливым и аридным условиям - Ахметов, И.3. (Вестник зоологии, 1977)
Functional state of thyroid gland was studied and compared in Rhombomys opimus Lichtenstein and Meriones libycus erythrourus Gray, in Citellus fulvis Lich. and Spermophilopsis leptodactylus L i c h. by means of radioactive iodine-131 and labelled thyroxine. Species, daily, and seasonal peculiarities of the functional activity of thyroid gland are determined in four species of rodents with different mode of life.